Karakter Penafsiran Fadil Salih Al-Samarra’i - Ali Hasan Siswanto (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2021)
This article was written by the author for several reasons. First, many academics are not familiar with the thought of Fadil Salih Al-Samarra’is interpretation, even though he is one of the commentators who live in the contemporary era. Second, The author thinks that the the Fadil Salih Al-Samarra’i method of interpretation is still not widely known by researchers. Therefore, the author examines one of his commentaries, namely ‘ala tariq al-tafsir al-bayani. The focus of this article is to understand the method of interpreting the Qur'an from the perspective of Fadil Salih Al-Samarra’i. To answer this, the author uses a qualitative-descriptive method with library research using the reading of the original interpretation of al-Samarra’i' in his book, namely al-haqiqat al-lughawiyyah, al-haqiqat al-'urfiyyah, al-haqiqat al-syar'iyyah.